Social Media for Lecturer Alternate Learning English in A Pandemic - Astuti, Peni (Fakultas Keguruan dan Ilmu Pendidikan Universitas Faletehan, 2021)
This article aims to describe the use of some social media networks as alternate adaptive learning of English, especially for English Education Study Program students. The Corona Virus (Covid-19) spread has had severe implications for the life sector, including education. Educational institutions should organize long-distance learning (PJJ – Pembelajaran Jarak Jauh) as a government effort to reduce the spread of Covid-19 in Indonesia. Lecturers, the leading academic actors in the University, must think creatively and innovatively to design PJJ to achieve learning objectives properly and optimally. This is relatively easy for lecturers and students, considering they are used to some of it. Given that not all educational institutions have an integrated learning platform; lecturers can adapt the function of social media as a medium for long distances learning (PJJ – Pembelajaran Jarak Jauh) during the Covid-19 pandemic. This study is based on a qualitative descriptive approach. Based on the research, lecturers and students used four relevant and familiar social media networks: Instagram, YouTube, WhatsApp and Tiktok. These four types of social media networks have characteristics that support the achievement of the four English skills (listening, speaking, reading and writing) through long-distance learning with their respective strengths and weaknesses.